تقييم اندمال كسور جدل الظنبوب المغلقة غير المختلطة عند البالغين بعد استخدام السفافيد القافلة المستبطنة للنقي و الصفائح المعدنية - جوني أحمد; يوسف صفوان; الدو مراد (Latakia University Journal -Medical Sciences Series, 2019)
Tibial shaft fractures are the most frequent fractures of long bones in the human body. The main objective of the study is to compare bone healing after surgical treatment of closed tibial shaft fractures in adults using either intramedullary nailing or plate fixation, to compare union related complications between the two methods , and to compare our results with the results of recent global studies . The study included adult patients diagnosed with closed non-complicated tibial shaft fractures admitted to the department of orthopaedic surgery at Tishreen University hospital in the years 2015 – 2016 – 2017 37 patients met our inclusion criteria and therefor they were included in the study . 22 patients were treated with intramedullary nailing and 15 patients were treated with plating . 20(54%) were males, 17(46%) were females . The majority of the cases (67.6%) were caused by high energy trauma . A detailed postoperative clinical and radiographic assessment was performed at one-and-a-half month intervals after surgery . The mean durations of surgery were equal in both groups at 80 minutes . The mean surgery preparation time and hospitalization time were shorter in the intramedullary nailing group ( 24 hours , 3 days respectively ). The Union-related complications percentage was higher in the plating group. The mean time to achieve union and the mean time to return to normal life activities were shorter in the intramedullary nailing group . intramedullary nailing offers a good choice for treatment of closed tibial shaft fractures in adults , and it allows early movement and weight bearing than plating only if it was applied according to the right indication . تُعتبَر كسور جدل الظنبوب أكثر كسور العظام الطويلة في جسم الإنسان شيوعاً ، والهدف الأساسي من الدراسة هو مقارنة اندمال كسور جدل الظنبوب المغلقة غير المختلطة عند البالغين بعد استخدام كل من السفافيد القافلة المستبطنة للنقي و الصفائح المعدنية و ذلك من حيث زمن العودة إلى الحياة الاعتيادية ، و مقارنة الاختلاطات المتعلقة بالاندمال بين طريقتي العلاج ، والمقارنة مع الدراسات العالمية ، شملت الدراسة المرضى البالغين المشخصين بكسور جدل الظنبوب المغلق غير المختلط لحظة القبول بأذيات عصبية أو وعائية مرافقة ، و المقبولين في شعبة الجراحة العظمية بمشفى تشرين الجامعي في اللاذقية في الأعوام 2015 و 2016 و 2017 . شملت عينة البحث 37 مريض تم تقسيمهم لمجموعتين رئيستين حسب طريقة التثبيت المتبعة. 22 مريض تم علاجهم بالسفود القافل المستبطن للنقي و15 مريض تم علاجهم بالصفيحة المعدنية . من بين 37 مريضاَ ، كان عدد الذكور 20 (54 %) وعدد الإناث 17 (46 %). أغلب كسور جدل الظنبوب المغلقة كانت بسبب أذيات طاقة عالية كالسقوط من شاهق أو حوادث السير 25 مريض (67.6%) . تمت المتابعة الشعاعية والسريرية خلال شهر و نصف و 3 أشهر و 6 أشهر و 9 أشهر وسنة بعد العمل الجراحي. متوسط مدة العمل الجراحي في السفود و الصفيحة متساويان (80 دقيقة) ، لكن متوسط مدة التحضير قبل الجراحة ومدة الاستشفاء أقل في مجموعة السفود ( 24ساعة و 3 أيام على التوالي )، إختلاطات العلاج بالصفيحة أكثر من اختلاطات العلاج بالسفود ، حدث الاندمال في مجموعة السفود ضمن متوسط مدة أقل نسبياً من مجموعة الصفيحة وبالتالي زمن العودة إلى الحياة الاعتيادية كان أقل ضمن مجموعة السفود . تعتبر السفافيد خياراً مناسباً و عملياً لعلاج كسور جدل الظنبوب المغلقة عند البالغين و هي توفر ثباتية كافية و تسمح بالتحريك الباكر و تحميل الوزن بشكل أبكر من الصفيحة و ذلك إذا تم تطبيقها تحت الاستطباب المناسب .